ON PERIODS OF OSCILLATIONS IN δ SCUTI TYPE STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
In considering both commen-surability spectra of oscillation frequencies for 6 Set stars and the distribution of periods for these variables from Kotov's (1987) data, frequencies f1H, JF, f2H, 5/4 f f and 3/2 f F, are found, as well as their linear combinations. For 13 stars with two known periods identifications are carried out.